Corporate Governance, Financial Performance, Auditor Quality, and Tax Agresiveness Propensity - Niandari, Nanik; Herbowo, Herbowo (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The government continues to strive to increase tax revenue targets. These efforts were followed by the government's consistent efforts to minimize tax avoidance through PP 55 of 2022 by developing tax avoidance prevention instruments. This research was conducted to analyze the relationship between corporate governance, financial performance, and the quality of an entity's auditors on the entity's tendency to act tax aggressively. The dependent variable in this research is tax aggressiveness measured by the effective tax rate. The dependent variables are corporate governance (measured by the proportion of independent commissioners and number of audit committees), financial condition (measured by profitability and leverage), and audit quality (measured by dummy variables). Data analysis uses multiple linear regression analysis. The test results show that profitability has a positive effect, and leverage has a negative effect on the tendency for tax aggressiveness. Other variables, namely corporate governance and audit quality, are proven to have no influence on the tendency for tax aggressiveness.